Protein thermostability engineering. Issue 116 (15th December 2016) - Modarres, H. Pezeshgi; Mofrad, M. R.; Sanati-Nezhad, A.
Abstract : Using structure and sequence based analysis we can engineer proteins to increase their thermal stability. Abstract : The use of enzymes for industrial and biomedical applications is limited to their function at elevated temperatures. The principles of thermostability engineering need to be implemented for proteins with low thermal stability to broaden their applications. Therefore, understanding the thermal stability modulating factors of proteins is necessary for engineering their thermostability. In this review, first different thermostability enhancing strategies in both the sequence and structure levels, discovered by studying the natural proteins adapted to different conditions, are introduced. Next, the progress in the development of various computational methods to engineer thermostability of proteins by learning from nature and introducing several popular tools and algorithms for protein thermostability engineering is highlighted. Further discussion includes the challenges in the field of protein thermostability engineering such as the protein stability–activity trade-off. Finally, how thermostability engineering could be instrumental for the design of protein drugs for biomedical applications is demonstrated.